Induction of resistance in bell pepper by Saccharomyces cerevisiae and acibenzolar-S-methyl: activation of defense mechanisms, antioxidant enzymes, and accumulation of photosynthetic pigments - Posso Suárez, David Fernando; D-arck Melo Cavalcante Althoff, Bianca; Dos Anjos Verzutti Fonseca, João; Di Piero, Robson Marcelo (Biocontrol science and technology, 2025)
Bacterial spot, caused by Xanthomonas euvesicatoria pv. euvesicatoria (Xee), is a significant disease affecting pepper cultivation at all growth stages and leading to reduced yields. Management strategies primarily involve the use of resistant cultivars and agrochemicals, which can result in environmental contamination and selection of bacterial strains resistant to active ingredients. This study evaluated the protective effects and mechanisms of action of Saccharomyces cerevisiae and acibenzolar-S-methyl (ASM) in controlling bacterial spot. Pepper plants from Rubi Gigante and All Big cultivars were sprayed with a yeast suspension or ASM, followed by inoculation with Xee 3 days later. Control plants received distilled water before inoculation. The severity of the disease and the activity of defense-related enzymes, peroxidase (POX), catalase (CAT), polyphenoloxidase (PPO), and phenylalanine ammonia-lyase (PAL) were evaluated over time. The accumulation of chlorophyll a, b, and carotenoids was also analyzed. In Rubi Gigante, the yeast reduced disease severity by 25%, while ASM decreased it by 37% and increased POX and PPO activities. In All Big, yeast and ASM reduced the severity by 25% and 80%, respectively, but only the yeast activated PPO and POX. The yeast suspension reduced the chlorophyll b content in the plants of the Rubi Gigante cultivar. In All Big, the levels of chlorophyll a, b, and carotenoids were reduced after the application of yeast or ASM. These findings suggest that S. cerevisiae and ASM could effectively manage bacterial spot in pepper plants.